Selenium unmasks protective iron armor: A possible defense against cutaneous inflammation and cancer - Arbiser, Jack L. (Biochim Biophys Acta Gen Subj, 2018)
BACKGROUND: A link between selenium deficiency and inflammatory skin diseases have been noted by many, but this link is still not well understood. We have previously studied the efficacy of ceramide analogs, based on the fire ant venom Solenopsin A, against our psoriasis animal model. Treatment of animals with solenopsin analogs resulted in significantly improved skin as well as in a coordinate downregulation of selenoproteins, namely Glutathione Peroxidase 4 (GPX4). We thus hypothesize that ferroptosis may be a physiologic process that may protect the skin from both inflammatory and neoplastic processes. METHODS: We analyze and compare gene expression profiles in the GEO database from clinical skin samples taken from healthy patients and psoriasis patients (both involved and noninvolved skin lesions). We validated the gene expression results against a second, independent, cohort from the GEO database. RESULTS: Significant reduction in gene expression of GPX4, elevated expression of Nrf2 downstream targets, and expression profiles mirroring erastin-inhibition of Cystine/Glutamate Antiporter-System X(C) activity in psoriatic skin lesions, compared to both noninvolved skin and healthy patient samples, suggest an innately inducible mechanism of ferroptosis. CONCLUSIONS: We present data that may indicate selenoproteins, particularly GPX4, in resolving inflammation and skin cancer, including the novel hypothesis that the human organism may downregulate GPX4 and reactive oxygen (REDOX) regulating proteins in the skin as a way of resolving psoriasis and nonmelanoma skin cancer through increased reactive oxygen species. Further studies are needed to investigate ferroptosis as a possible physiologic mechanism for eliminating inflammatory and malignant tissues. GENERAL SIGNIFICANCE: This study provides a fresh framework for understanding the seemingly contradictory effects of selenium supplementation. In addition, it offers a novel explanation of how physiologic upregulation of ferroptosis and downregulation of selenoprotein synthesis may mediate resolution of inflammation and carcinogenesis. This is of therapeutic significance.